Recurrent respiratory infections in young school-age children and psychological maternal predictors - V.V. Kramarchuk; I.L. Vysochyna (Сучасна педіатрія: Україна, 2023)
Recurrent respiratory infections (RRIs) in children remain a pertinent issue in modern medicine. According to literary data, the prevalence of this phenomenon can reach up to a quarter of the child population. RRIs adversely affect a child’s physical development, social adaptation, and give rise to intra-family conflicts.